Strategi Pengembangan Komponen Kurikulum Bahasa Arab - Mochamad Syaifudin (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2017)
This paper is intended to provide a holistic view on the strategies and processes of Arabic curriculum development component by reconcidering the foundations of its development. For this reason, this paper starts to reconsider the philosophical foundation, psychological foundation, socio-cultural foundation, science and technological foundation, which then be elaborated by mulling the principles of curriculum development component, which are relevance, flexibility, continuity, efficiency, and effectiveness. Hence, the process of Arabic curriculum development component could be executed through the approaches of academic, humanity, technology, and even social reconstruction. These approaches, for the author, are able to reconstruct the curriculum to be such a relevant and accommodative one toward the needs of society and the demands of today's era.